2010
DOI: 10.2174/138161210791959917
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmaceutical Economics of Child Psychiatric Drug Treatment

Abstract: The last decade, the number of health economic evaluations has increased substantially in the field of child psychiatry. The objective of the present paper is to offer an overview of economic evaluations of child psychiatric drug treatment. Major electronic databases, as well as abstract booklets from international clinical and health economics conferences with an external peer review process, were examined to search for comparative economic evaluations of child and adolescent psychiatric drug treatment. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 192 publications
(260 reference statements)
0
3
0
Order By: Relevance
“…However, these disorders are less well served by cost‐related research than ASD, CD or ADHD, although both have implications for poorer adult health and quality of life. The question of how best to use resources to treat these disorders in childhood also remains unanswered, even when considering medication (see also, Schlander, ; p2455). This absence of research evidence hampered provision of value for money advice to health policy makers in Australia and the authors had to draw on adult studies for some parameters in their analysis of childhood depression (p. e724, Mihalopoulos, Vos, Pirkis, & Carter, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these disorders are less well served by cost‐related research than ASD, CD or ADHD, although both have implications for poorer adult health and quality of life. The question of how best to use resources to treat these disorders in childhood also remains unanswered, even when considering medication (see also, Schlander, ; p2455). This absence of research evidence hampered provision of value for money advice to health policy makers in Australia and the authors had to draw on adult studies for some parameters in their analysis of childhood depression (p. e724, Mihalopoulos, Vos, Pirkis, & Carter, ).…”
Section: Resultsmentioning
confidence: 99%
“…They also suggest that to develop the limited evidence base, guidelines might improve the quality of economic evaluations, and help ensure that an economic evaluation always accompanies an effectiveness study. Four other focussed reviews of economic evaluations have been published since 2009: two considered the economic evidence for parenting programmes to intervene in childhood behaviour problems (Charles et al., ; Stevens, ); and two reviewed studies of medication (Schlander, ; Wu et al, ). All four of these reviews found full cost‐effectiveness analyses to be rare and methodological problems to be common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation